Enhancing the Nutritional Composition and Phenolic Compound Content of Sprouted Chickpeas Using Sucrose and Chitosan as Elicitors - Alejandra Linares-Castañeda; Luis Jorge Corzo-Ríos; Ana Elena Cedillo-Olivos; Xariss M. Sánchez-Chino; Rosalva Mora-Escobedo; Cristian Jiménez-Martínez (Molecules)
The use of elicitors during germination is a strategy to enhance the nutritional quality and biofunctional properties of various legumes, such as chickpeas, which are important sources of proteins and bioactive compounds. The objective of this study was to evaluate the effect of the use of chitosan (CH) and sucrose (SU) during sprouting on protein content, in vitro protein digestibility (IVPD), total phenolic content (TPC), and antioxidant activity (AOX). For this purpose, soaking time, elicitor concentration (CH or SU), and sprouting time were optimized to obtain maximum values for the response variables. The results showed that the optimal conditions for achieving increases in nutritional and biofunctional properties were 1 h of soaking, 0.35% w/v, and 5 days of sprouting for CH, and 2.55 h of soaking, 1% w/v, and 5 days of sprouting for SU. Under these conditions, protein content increased by 7–12%, IVPD by 78–86%, TPC by 379–327%, and AOX by 115% for CH and SU, respectively. Additionally, morphological changes were observed in the cellular structure of chickpea cotyledons, but no changes were detected in the crystalline structure of starch. These results contribute to the understanding of the effect of CH and SU in modifying the nutritional and biofunctional properties of chickpeas.